Selected Topics in Applied Econometrics - (:unkn) unknown (Peter Lang AG, 2019)
This book aims to bring together studies using different data types (panel data, cross-sectional data and time series data) and different methods (for example, panel regression, nonlinear time series, chaos approach, deep learning, machine learning techniques among others) and to create a source for those interested in these topics and methods by addressing some selected applied econometrics topics which have been developed in recent years. It creates a common meeting ground for scientists who give econometrics education in Turkey to study, and contribute to the delivery of the authors' knowledge to the people who take interest. This book can also be useful for «Applied Economics and Econometrics» courses in postgraduate education as a material source. © Peter Lang AG 2019.